DINAMIKA SOSIAL PEDAGANG DI PASAR BLAURAN KOTA PALANGKA RAYA - Sriyana Sriyana; Bumbun Bumbun (JURNAL SOCIOPOLITICO, 2021)
The descriptive study of Blauran Traditional Market Traders in Palangka Raya City was motivated by problems arising from the rapid emergence of modern markets which were feared to shift the existence of traditional markets in Palangka Raya City. Where the problems that occur in traditional markets greatly affect the existence of the traditional markets themselves, from the problems of services provided by traders to the most frequent problems that arise, namely regarding the cleanliness in traditional markets. This study aims to describe and analyze the social dynamics of traders in the Blauran traditional market, Palangka Raya City. While the research method is a qualitative method with a descriptive approach, with data collection techniques through interviews, observation and documentation study. The results showed that the Blauran traditional market traders instilled values ​​and norms that had existed from generation to generation from generation to generation before them. So that traders can easily overcome problems that arise as a result of the emergence of modern markets, and with the development of the era traders provide other innovations from pre-existing values ​​and practice them directly to buyers in order to provide comfort obtained from the work ethic produced directly by traders.